SODSEEDING OF OATS (Avena strigosa Schreb.) AND ANNUAL RYEGRASS (Lolium multiflorum Lam.) INTO NATIVE PASTURE WITH AND WITHOUT THE USE OF PARAQUAT - SCHLICK, FÁBIO EDUARDO (2000)
The experiment was conducted on a native pasture in Santa Maria, Rio Grande do Sul State, Brazil. The soil is a Red Yellow Podzolic. The climate of the region is Cfa, subtropical umid. Treatments were the introduction by sodseeding of oats (Avena strigosa) and annual ryegrass (Lolium multiflorum) into native pasture, with and without dosis of paraquat. The seeding and fertilization were made with a sod-seeder drill, after herbicide aplications on 04/21/98. The experimental design was a randomized complete blocks with Eive replications. It was evaluated dry matter yield (DM), botanical composition, plant and tiller populations of sodseeded species, crude protein content (CP), in vitro organic matter digestibility (IVOMD) and seed yield for natural reseeding. No significant differences were found for all the parameters studied. Pasture average DM yield was 4784 kg/ha. CP content and IVOMD were 13% and 58%, respectively. Ryegrass average seed yield was 287 kg/ha.